The Influence of Capital, Number of Working Hours, Works Force and Time to Run Business on Operating Income of Angkringan in Yogyakarta - Utik Bidayati; Salamatun Asakdiyah (Forum Manajemen Indonesia (FMI), 2015)
Informal business sector is the largest economic activity unit in Indonesia. Most informal businesses have earned no more than five million rupias per year. One form of informal business sector is angkringan. Angkringan is one of informal business forms that sales foods and drink to lower-middle-class consumers . This type of business is mostly done in Jogjakarta. This business is the main source of income some communities in Jogjakarta. This research is aimed to analyze the influence of capital, number of working hours, work force, and time to run the business on operating income of angkringan. The sample was collected by using purposive sampling method. The respondents are 70 angkringan owners in Jetis, Yogyakarta. Data collection was carried out by distributing questionnaire to respondents about their operating income, amount of their capital, working hours, and work force. Analysis instrument used in this research is multiple regression analysis, while the hypothesis is tested by using t test and F test. Data on this research is cross sectional. To obtained better result better, the amount of business capital and operating income are transformed into a logarithm. Model of multiple regression is formulated as a log y = 4,113 + 0,283 Log x1 + 0,006x2 + 0,093x3 + 0,012x4. The result of the study showed that income level of angkringan sellers in Jetis, Yogyakarta, is influenced by the amount of business capital, working hours, work force and time to run their business. Number of working hours is the greatest influencing factor on angkringan income. The result of testing the regression coefficient in partial and unison shows that all variables significantly impact the income level angkringan sellers in Jetis, Yogyakarta. The coefficients determination (r2) result reaches 32.5%. While the remaining 67.5% described by other variables is not included in the model research. Key word: Influence of capital, number of working hours, works force and time to run business, bboperating income